UK mothers' experiences of bottle refusal by their breastfed baby - Clare Maxwell; Kate M. Fleming; Valerie Fleming; Lorna Porcellato (Wiley, 2020)
Abstract Little is known about bottle refusal by breastfed babies; however, an informal review of global online forums and social media suggested large numbers of mothers experiencing the scenario. This study aimed to explore UK mothers' experiences of bottle refusal by their breastfed baby in order to provide understanding of the scenario and enhance support for mothers experiencing it. A 22‐point online questionnaire was developed and completed by 841 UK mothers. Findings suggest that mothers introduced a bottle to their breastfed baby due to physical, psychological and socio‐cultural factors. Advice and support for mothers experiencing bottle refusal was not always helpful, and 27% of mothers reported bottle refusal as having a negative impact on their breastfeeding experience. When compared with eventual bottle acceptance, bottle refusal was significantly associated with previous experience of bottle refusal (p < .001), how frequently mothers intended to feed their baby by bottle and babies being younger at the first attempt to introduce a bottle (p < .001). This study provides a unique insight into the complexities of bottle refusal by breastfed babies and the impact it can have upon mothers' breastfeeding experiences. It generates knowledge and understanding that can help to inform practice and policies. In addition, a 'normalising' of the scenario could enable mothers, and those supporting them, to view and manage it more positively.